Separator Modified by Cobalt‐Embedded Carbon Nanosheets Enabling Chemisorption and Catalytic Effects of Polysulfides for High‐Energy‐Density Lithium‐Sulfur Batteries. Issue 32 (17th July 2019) - Cheng, Zhibin; Pan, Hui; Chen, Jinqing; Meng, Xueping; Wang, Ruihu
Abstract: Lithium‐sulfur (Li‐S) batteries are considered to be one of the promising next‐generation energy storage systems. Considerable progress has been achieved in sulfur composite cathodes, but high cycling stability and discharging capacity at the expense of volumetric capacity have offset their advantages. Herein, a functional separator is presented by coating cobalt‐embedded nitrogen‐doped porous carbon nanosheets and graphene on one surface of a commercial polypropylene separator. The coating layer not only suppresses the polysulfide shuttle effect through chemical affinity, but also functions as an electrocatalyst to propel catalytic conversion of intercepted polysulfides. The slurry‐bladed carbon nanotubes/sulfur cathode with 90 wt% sulfur deliver high reversible capacity of 1103 mA h g −1 and volumetric capacity of 1062 mA h cm −3 at 0.2 C, and the freestanding carbon nanofibers/sulfur cathode provides a high discharging capacity of 1190 mA h g −1 and volumetric capacity of 1136 mA h cm −3 at high sulfur content of 78 wt% and sulfur loading of 10.5 mg cm −2 . The electrochemical performance is comparable with or even superior to those in the state‐of‐the‐art carbon‐based sulfur cathodes. The separator reported in this work holds great promise for the development of high‐energy‐density Li‐S batteries. Abstract : A modified separator in lithium‐sulfur batteries is presented through coating cobalt‐embedded nitrogen‐doped porous carbon nanosheets and graphene on one surface of commercial polypropylene separator. Benefiting from the high electronic conductivity of coating layer and catalytic effects of cobalt nanoparticles, high volumetric capacity, outstanding rate capability, and remarkable cycling stability are synchronously achieved in both slurry‐bladed and freestanding electrodes.